ANALISIS STRATEGI PENDIDIKAN KARAKTER, KEPRIBADIAN DAN PROFESIONALISME TARUNA MELALUI HUKUMAN PREVENTIF - Makmur Makmur; Muchlies Muhayyang; Poerwanto Poerwanto (Journal of Education on Social Science (JESS), 2023)
Discipline and exemplary must be carried out continuously or habitually to create a character. Character education strategies require tools/media to implement them. The tool is in the form of rules, regulations, norms, and existing ethics. Cadets are among the representatives of a generation that demands high quality and performance. Cadets are essential in deciding a nation's progress since an advanced nation has a high degree of quality people resources, praiseworthy character, and a strong and resilient mental attitude. This study aims to find out how the application of character education to the formation of personality and professionalism of cadets in carrying out education and to find out the options/views that can be developed in character education, personality, and professionalism of cadets. This research used a descriptive approach. The data was collected from interviews, field notes, personal documents, notes or memos of researchers, and other supporting official documents. The results of this study in the form of character education factors explain the variance of 48,437%. Personality factors can explain the variance of 15,635%. The professionalism factor is the third factor, with an eigen of 3,591 and a variance value of 38,129%. The Preventive Punishment factor is the fourth factor that has a variance of 25,456%. It can be concluded that the analysis of several factors in determining cadets' character education strategy, personality, and professionalism, with preventive punishments, is carried out with rules, recommendations and orders, prohibitions, and discipline.